Peripheral fatigue limits endurance exercise via a sensory feedback-mediated reduction in spinal motoneuronal output - Amann, Markus (American Physiological Society, 2013)
This study sought to determine whether afferent feedback associated with peripheral muscle fatigue inhibits central motor drive (CMD) and thereby limits endurance exercise performance. On two separate days, eight men performed constant-load, single-leg knee extensor exercise to exhaustion (85% of peak power) with each leg (Leg(1) and Leg(2)). On another day, the performance test was repeated with one leg (Leg(1)) and consecutively (within 10 s) with the other/contralateral leg (Leg(2)-post). Exercise-induced quadriceps fatigue was assessed by reductions in potentiated quadriceps twitch-force from pre- to postexercise (ΔQ(tw,pot)) in response to supramaximal magnetic femoral nerve stimulation. The output from spinal motoneurons, estimated from quadriceps electromyography (iEMG), was used to reflect changes in CMD. Rating of perceived exertion (RPE) was recorded during exercise. Time to exhaustion (∼9.3 min) and exercise-induced ΔQ(tw,pot) (∼51%) were similar in Leg(1) and Leg(2) (P > 0.5). In the consecutive leg trial, endurance performance of the first leg was similar to that observed during the initial trial (∼9.3 min; P = 0.8); however, time to exhaustion of the consecutively exercising contralateral leg (Leg(2)-post) was shorter than the initial Leg(2) trial (4.7 ± 0.6 vs. 9.2 ± 0.4 min; P < 0.01). Additionally, ΔQ(tw,pot) following Leg(2)-post was less than Leg(2) (33 ± 3 vs 52 ± 3%; P < 0.01). Although the slope of iEMG was similar during Leg(2) and Leg(2)-post, end-exercise iEMG following Leg(2)-post was 26% lower compared with Leg(2) (P < 0.05). Despite a similar rate of rise, RPE was consistently ∼28% higher throughout Leg(2)-post vs. Leg(2) (P < 0.05). In conclusion, this study provides evidence that peripheral fatigue and associated afferent feedback limits the development of peripheral fatigue and compromises endurance exercise performance by inhibiting CMD.